Seasonal abundance and distribution patterns of common bottlenose dolphins (Tursiops truncatus) near St. Joseph Bay, Florida, USA - Balmer , B. C.; Wells , R. S.; Nowacek , S. M.; Nowacek , D. P.; Schwacke , L. H.; Mclellan , D. A.; Scharf , F. S.; Rowles , T. K.; Hansen , L. J.; Spradlin , T. R.; Pabst , D. A. (J. Cetacean Res. Manage., 2023)
Three unusual mortalities events involving bottlenose dolphins (Tursiops truncatus Montagu 1821) occurred along Florida’s northern Gulf of Mexico coast between 1999 and 2006. The causes of these events, in which over 300 bottlenose dolphins are known to have died, are still under investigation. The impact of these mortality events cannot be fully evaluated, because little prior information on bottlenose dolphin abundance and distribution patterns exist in this region. Thus, the goals of this study were to estimate seasonal abundance, develop site-fidelity indices, and describe distribution patterns of bottlenose dolphins in St. Joseph Bay, Gulf County, Florida, USA. This study site was chosen because it was impacted by all three unusual mortality events and was the geographic focus of the 2004 event. Mark-recapture photo-identification surveys were conducted across multiple seasons from February 2005 through July 2007. Site-fidelity indices were calculated for each identifiable dolphin based upon all photo-ID efforts undertaken in the area. Distribution patterns were investigated by short-term (12-94 days) radio-tracking of tagged individuals across seasons (April-July, n=9; July-October, n=15). Mark-recapture closed and robust abundance estimates, as well as site-fidelity indices suggest that St. Joseph Bay supports a resident community of 78-152 bottlenose dolphins. During spring and autumn, this region experiences an influx of dolphins, as demonstrated by closed and robust abundance estimates of 313-410 and 237-340, respectively. These results are supported by the distribution patterns of radio-tagged individuals. Individuals tagged in summer tended to stay within or near St. Joseph Bay, whereas two individuals tagged in spring ranged more than 40km from the study site. This study provides the first detailed examination of bottlenose dolphin abundance and distribution patterns for this region of the northern Gulf coast of Florida. These results suggest that unusual mortality events probably had, and will in the future have, seasonally variable effects on bottlenose dolphins in St. Joseph Bay. Future mortality events that occur during the summer and winter in St. Joseph Bay may predominantly affect resident individuals, while those that occur during the spring and autumn will probably affect both residents and seasonal visitors.